Utilization of ICT in Learning the History of Islamic Culture - Le Liam; Huang Hui; Lewin Carsten (Yayasan Adra Karima Hubbi, 2023)
Information and communication technology is an extensive umbrella terminology that covers all technical equipment for processing and conveying Information which includes two aspects, namely information technology and communication technology, to help process important Information such as information transfer activities. In this article, we will discuss the benefits of information and communication technology in learning the history of Islamic culture. This research aims to describe the benefits of information and communication technology in learning the history of Islamic culture. Moreover, this study uses a quantitative method that can explain the benefits of information and communication technology in learning the history of Islamic culture by conducting in-depth interviews. This study's results describe the benefits of information and communication technology in learning Islamic cultural history, which makes learning Islamic cultural history more exciting and fosters the attractiveness of students studying Islamic cultural history. The limitation of this research is that the researcher only describes the benefits of information and communication technology in learning Islamic cultural history. The researcher hopes that future researchers can explain the benefits of information and communication technology in other subjects.